Deteksi Kerusakan Pada Plat Dengan Menggunakan Sinyal Suara - Madi Harto Silalahi; Feblil Huda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Structural Health Monitoring (SHM) is a process of identifying damage by Nondestructive Evaluation (NDE). The method can be done by non-contact method. In this study a non-contact method was proposed to monitor the specimen by utilizing the sound signal as an excitation. This method has advantage becauseit is not costly toset-up testing.Excitation is given to specimen by the loudspeaker. The sound response on the specimen is recorded through the microphone. Recorded data in the form of time domain is transformed into a frequency domain using FFT (Fast Fourier Transform) method. The domain data frequency response and data excitation frequency can be processed into data of FRF(Frequency Response Function).FRF matrix form is used to estimate the mode shape. The first Natural frequency of mode shape is transformed to detect the location of damage. The study was performed on specimen under normal and damaged conditions. The result of the research on simulation and testing show that proposed method can detect the location of the damage properly and accurately. Keywords: Signal Sound, SHM,FFT,FRF,Mode Shape